Deradikalisasi Agama: Proses Pelembagaan Nilai-Nilai Agama Pada Siswa SMA Di Kota Padang - Darmaiza, Darmaiza; Idris, Mhd. (AL-ADYAN, 2020)
The exclusiveness of religious understanding cannot be separated from the transformation of values obtained by individuals on the bench of formal education. Actually, religious education in the schools is provided in short time, only two hours a week. As a consequence, if they do not get additional religious lessons from parents or religious teachers in their environment, it is also possible for these children to seek wild understanding of religion in the midst of the swift flow of digital media and the internet. The survey research results from the Islamic Studies and Peace Institute (LaKIP) Jakarta 2010 need to be underlined. His findings are really worrying, that almost half of students in Jabodetabek expressed their agreement to radical actions. This study aims to determine how the process of institutionalizing religious values in students high school in the city of Padang. The method used in this study is a qualitative method and snowball technique as a sampling technique. While data collection using interview methods and field documentation. Data obtained from the results of the interview will be transcribed and then reduced to select the appropriate data so that the data presented is representative. After doing research, it was found that the values of diversity have been applied to every activity in the school such as reading al-Qur`an and Asmaul Husna before starting lessons, circumcision Duha prayer, obligatory prayer in congregation, Graduation Tahfizh and others. From interviews with students in the sample schools it was found that 100% of them rejected the understanding of radicalism. The 60% rejection benchmarks are religion, 30% are law and law and 10% are on other grounds.